Analisis Faktor yang Berhubungan dengan Pelaksanaan Manajemen Nyeri Non Farmakologis Oleh Perawat Pelaksana di Irna Non Bedah RSUP Dr M Djamil Padang Tahun 2015 - Fitria Fajriani; Yulastri Arif; Deswita Deswita (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The comfort rate of patients or patients free from pain is one indicator of the quality of health services in inpatient rooms. One of the nurse's efforts to improve the quality rate is non-pharmacological pain management. Non-surgical Irna has a fairly high pain rate, but the number of pain management performed by nurses is still low. The purpose of this study was to analyze the factors associated with the implementation of non-pharmacological pain management by nurses at Irna Non-Surgical. This study uses an analytical design with a Cross Sectional approach. The sample of this study was 89 people who were taken purposively. This research instrument was made by researchers who have been tested for validity and reliability. The results showed that more than half (59.6%) of nurses were not good at implementing non-pharmacological pain management. Based on the Chi-square statistical test, there is a significant relationship between training, knowledge, attitudes and motivation towards the implementation of non-pharmacological pain management with each P-value (0.001; 0.007; 0.001; 0.001). The factor that has the greatest contribution to the implementation of non-pharmacological pain management is training. Therefore, it is expected that service institutions can create sustainable training programs on non-pharmacological pain management.